Analysing the professional negligence of architects in the construction industry in Malaysia: a comparative study with the position in Singapore / Nur Adilla Ruslan… [ et al. ] - Ruslan, Nur Adilla; Ismail, Nurul Hafizah; Abdul Rahman, Amir Hamzah; Abdullah, Nor Asyikin (Faculty of Law, 2013)
Construction failure has always been associated with the negligent act of an architect in conducting their duties. This perception has long been emerged in the mind of the society in Malaysia particularly. This can be seen when a building collapsed the first person to be pointed out will be the architect despite other persons such as engineers and quantity surveyor or the contractor that also had contributed their work to the building up of the said building. Thus, it has reflected a bad perspective on architects in Malaysia conducting their duties. The purpose of this study is to determine the roles of architects in Malaysia by making a comparison with the law in Singapore to identify its relation with the current situation of construction failure in Malaysia. It is necessary to make the comparison as to identify whether there is any need for improvement in the current law or whether there are other factors that could contribute to the construction failure in Malaysia. We will also examine the previous cases to relate with the actual roles and duties of architects both in Singapore and Malaysia. In conclusion we will examine how the implementation of the existing laws in Malaysia as well as in Singapore.